(untitled) (Technological Innovations Journal, 2023)
An experiment was conducted to obtain copper (II) ions in a basic environment using ethylenediaminetetraacetic acid (EDTA) and oxidized copper minerals from Cerro Azoguini in Puno, Peru. Specific objectives included investigating the solubility of Cu2+ ions in a mineral with high silica, limestone, and iron content, as well as studying the influence of pH, EDTA concentration, and extraction time. 1.5 grams of ground mineral at -100 mesh (150 µm), with 80% pass and 6% solids, were leached with a 0.5 M NaHCO3 solution at different pH levels and EDTA concentrations. The results indicated the extraction of 3.5 g/L of Cu2+ ions at pH 10 with 0.12 M EDTA, without agitation, at room temperature (19°C), over a period of 83 hours. It was observed that the NaHCO3 solution extracted copper from the mineral, and EDTA quickly chelated it, forming ionic complexes such as CuHEDTA ∧ (1−), CuHEDTA ∧ (2−) and Cu0HEDTA ∧ (3−). Other metals present in the gangue were not chelated by EDTA, demonstrating its high selectivity based on solubility constants and precipitation formation at different pH levels. Additionally, high copper extraction rates were obtained at a pH of 13.15, possibly due to decreased protons and increased ions from both the reagent and leached mineral. In conclusion, the physicochemical analyses revealed the feasibility of obtaining Cu2+ ions by solubilizing oxidized minerals, followed by rapid chelation with EDTA to form diverse metal complexes depending on the pH of the medium.